Carbohydrate and sleep: An evaluation of putative mechanisms - Benton, David; Bloxham, Anthony; Gaylor, Chantelle; Brennan, Anthony; Young, Hayley A. (Frontiers in Nutrition, 2022)
Sleep problems are extremely common in industrialized countries and the possibility that diet might be used to improve sleep has been considered. The topic has been reviewed many times, resulting in the frequent suggestion that carbohydrate increases the uptake of tryptophan by the brain, where it is metabolized into serotonin and melatonin, with the suggestion that this improves sleep. An alternative mechanism was proposed based on animal literature that has been largely ignored by those considering diet and sleep. The hypothesis was that, as in the hypothalamus there are glucose-sensing neurons associated with the sleep-wake cycle, we should consider the impact of carbohydrate-induced changes in the level of blood glucose. A meta-analysis found that after consuming a lower amount of carbohydrate, more time was spent in slow-wave sleep (SWS) and less in rapid-eye-movement sleep. As the credibility of alternative mechanisms has tended not to have been critically evaluated, they were considered by examining their biochemical, nutritional, and pharmacological plausibility. Although high carbohydrate consumption can increase the uptake of tryptophan by the brain, it only occurs with such low levels of protein that the mechanism is not relevant to a normal diet. After entering the brain tryptophan is converted to serotonin, a neurotransmitter known to influence so many different aspects of sleep and wakefulness, that it is not reasonable to expect a uniform improvement in sleep. Some serotonin is converted to melatonin, although the exogenous dose of melatonin needed to influence sleep cannot be credibly provided by the diet. This review was registered in the International Prospective Register of Systematic Reviews (CRD42020223560).